Features of adaptation to intensive physical load of skilled cyclists specializing in mountain bike - Kvashuk, P. V.; Voronov, A. V.; Semaeva, G. N.; Malkin, R. V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the features of the adaptation of the neuromuscular apparatus and vegetative functions to physical activity of progressively increasing power and the mechanisms for maintaining the performance of qualified cyclists specializing in mountain biking.